DPR Recycling Collar for Simpler and Brighter RGBW Pico Projectors. Issue 1 (June 2014) - Li, Kenneth
Abstract Traditional pico projector with RGB LEDs uses color multiplexers with dichroic filters and collimating lenses for combining the colored lights, is complex and costly. This paper describes a new LED recycling collar using Dual Parabolic Reflector (DPR) developed to increase the brightness of multicolored LED package with RGBW LEDs with output from each LED recycles back into itself on the same location, thus increases the brightness of each LED independently. In addition, the unique possibility of using the white LED in the multiplexed output provides another dimension in the color scheme, increasing the output brightness. The smaller component count lowers the cost of the system. A DLP projector using this DPR recycling collar will be described.